STRATEGI PENGEMBANGAN SARANA REKREASI OBJEK WISATA PANTAI AIR MANIS PADANG - Yuspita, Ela (RC-INSTITUT, 2019)
This research originated from observations of researchers on recreational facilities in the form of playing facilities in the tourist attractions of Air Manis Beach Padang. This type of research is a qualitative descriptive study with a survey method. The sample source data from this study is the management of tourist objects, namely the Department of Tourism and Culture of the City of Padang, the community around the attractions of Padang Air Manis Beach and visitors to the attractions of Air Manis Beach Padang. The sample collection technique uses purposive sampling. Data collection techniques are carried out by observation, interviews, and documentation. Furthermore, the data were analyzed by the Miles and Huberman data analysis techniques by performing three stages, namely: data reduction, data display and conclusion drawing. The results of the study concluded that in general the attractions of Padang Air Manis Beach have strength that supports the development of recreational facilities in the form of government support by providing direction for the community. Weaknesses in the condition of human resources that have less role in managing and developing this object. Whereas opportunities with a strategic place with adequate natural resources and the availability of a very wide tourist area that can be used to build recreational facilities in the form of play facilities are a great opportunity for the development of recreational facilities so that it will increase income / income for the community or local government. . But there is also a threat, there are similarities in the game facilities that are established in other tourist objects that are close to the attractions of Air Manis Beach Padang, if no effort is made to maintain and improve the quality of this tourist attraction there will be a decrease in tourist visits to the object this tour. So it is necessary to develop a recreational facility for tourism objects in Air Manis Beach, Padang. Keywords: Strategy, Development, Recreational Facilities